Use of standardized nasal and skin decolonization to reduce rates of bacteremia in patients undergoing extracorporeal membrane oxygenation - Madyson Taylor; Russell L Griffin; Jeremey Walker; Catina James; Angela Akinsanya; Mary Duncan; Rachael A Lee (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract